Identification and Prevalence of Digestive Tract Endoparasites of Goats in Ujungpangkah, Gresik District - Muhammad Fahmi Abdillah; Nunuk Dyah Retno Lastuti; Suzanita Utama; Endang Suprihati (Journal of Parasite Science (JoPS), 2021)
This study aims to determine the prevalence and species of endoparasite that infect the digestive tract of goats in Ujungpangkah Sub-District, Gresik District. This study was conducted in February-March 2021 with 100 samples of goat’s stool. Sample examination was conducted in the laboratory of the Division of Veterinary Parasitology, Faculty of Veterinary Medicine, Universitas Airlangga. In fecal examination found four types of endoparasites, which were: Eimeria sp. 62%, Blastocystis sp. 5%, Haemonchus sp. 4%, Strongyloides sp. 2% and mixed infection prevalence was 3%. This study showed a prevalence of 76% digestive tract endoparasite. The Chi-Square test showed significant differences (p <0.05) between groups of goats aged under one year (57%) and over one year (43%).